Availability of pre-admission information to prospective graduate students in speech-language pathology. Issue 4 (3rd July 2016) - Tekieli Koay, Mary Ellen; Lass, Norman J.; Parrill, Madaline; Naeser, Danielle; Babin, Kelly; Bayer, Olivia; Cook, Megan; Elmore, Madeline; Frye, Rachel; Kerwood, Samantha
ABSTRACT: An extensive Internet search was conducted to obtain pre-admission information and acceptance statistics from 260 graduate programmes in speech-language pathology accredited by the American Speech-Language-Hearing Association (ASHA) in the United States. ASHA is the national professional, scientific and credentialing association for members and affiliates who are audiologists; speech-language pathologists; speech, language and hearing scientists; audiology and speech-language pathology support personnel and students. Data were collected for analysis from Internet websites of individual academic programmes and ASHA's EdFind, an online directory for undergraduate and graduate programmes in communication sciences and disorders in the United States. Frequency counts were used to analyse the data. Since graduate programmes are not required by ASHA to report or publish entrance requirements, the information included on the individual websites and ASHA's EdFind varies widely among the programmes with some information incomplete or not reported at all.